Regulation of Fto/Ftm gene expression in mice and humans. - Stratigopoulos, G; Padilla, S; LeDuc, C; Watson, E; Hattersley, A; McCarthy, M; Zeltser, L; Chung, W; Leibel, R (2008)
Two recent, large whole-genome association studies (GWAS) in European populations have associated a approximately 47-kb region that contains part of the FTO gene with high body mass index (BMI). The functions of FTO and adjacent FTM in human biology are not clear. We examined expression of these genes in organs of mice segregating for monogenic obesity mutations, exposed to underfeeding/overfeeding, and to 4 degrees C. Fto/Ftm expression was reduced in mesenteric adipose tissue of mice segregating for the Ay, Lep ob, Lepr db, Cpe fat, or tub mutations, and there was a similar trend in other tissues. These effects were not due to adiposity per se. Hypothalamic Fto and Ftm expression were decreased by fasting in lean and obese animals and by cold exposure in lean mice. The fact that responses of Fto and Ftm expression to these manipulations were almost indistinguishable suggested that the genes might be coregulated. The putative overlapping regulatory region contains at least two canonical CUTL1 binding sites. One of these nominal CUTL1 sites includes rs8050136, a SNP associated with high body mass. The A allele of rs8050136 preferentially bound CUTL1[corrected] in human fibroblast DNA. 70% knockdown of CUTL1 expression in human fibroblasts decreased FTO and FTM expression by 90 and 65%, respectively. Animals and humans with various genetic interruptions of FTO or FTM have phenotypes reminiscent of aspects of the Bardet-Biedl obesity syndrome, a confirmed "ciliopathy." FTM has recently been shown to be a ciliary basal body protein.